THE EFFECT OF GREEN ACCOUNTING ON COMPANY REPUTATION WITH INTELLECTUAL CAPITAL AS A MODERATION - Rabbani, Mohammad Farhanudin; Wuryaningsih, Wuryaningsih (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to determine the effect of environmental performance, environmental disclosure, and environmental costs on corporate reputation moderated by intellectual capital. This study uses a quantitative approach with basic material and energy sector companies listed on the IDX for 2019 – 2021. The results of this study indicate that environmental performance, environmental costs and intellectual capital have no effect on company reputation. These findings indicate that stakeholders and shareholders do not prioritize environmental performance as the main aspect in the assessment to invest in a company. Environmental disclosure has a positive effect on company reputation. This is because environmental disclosure is a way of communicating by the company to the public and stakeholders regarding the environmental and social impacts arising from the company's economic activities to the wider community and stakeholders which will form a good corporate reputation. Intellectual capital is not able to moderate the relationship between environmental performance, environmental disclosure, and environmental costs on company reputation.